The Prospective Effects of the Free Trade Agreement between Colombia and South Korea on the Colombian Automotive Sector (2018)
This article evaluates the effects of the Free Trade Agreement (FTA) between Colombia and South Korea in the Colombian automotive sector and analyzes some possible prospective effects in the short and medium term. Results were extracted using a mixed methodology, including interviews, literature review, report of the Colombian Association of Motor Vehicles and Trademap analysis.